Analisis Elastisitas Permintaan, Elastisitas Silang, dan Elastisitas Pendapatan pada UMKM Medan - Florentina Sitompul; Fiyasti Mawdatul Khairia; Jese Marvel Lumban Tobing; Khairani Alawiyah Matondang (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This study aims to analyze demand elasticity, cross elasticity, and income elasticity in Micro, Small, and Medium Enterprises (MSMEs) in Medan City. Demand elasticity measures the sensitivity of demand to changes in product prices, while cross elasticity evaluates the impact of price changes of other products on the demand for a particular product. Income elasticity assesses how demand changes in response to changes in consumer income. Using primary data collected from surveys of MSME entrepreneurs, the results show that most MSME products exhibit elastic demand, indicating significant dependence on price. Additionally, positive and negative cross-relationships were found between some products, reflecting substitution and complementarity. Income elasticity revealed that the majority of MSME products are categorized as normal goods, although some fall into the inferior goods category. These findings provide valuable insights for MSMEs in formulating pricing strategies, product diversification, and targeting consumers based on their income levels.